1996
DOI: 10.3904/kjim.1996.11.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Interstitial Pneumonia/Fibrosis: Clinical Manifestations, Histologic and Radiologic Features

Abstract: ObjectivesCustomarily used classification of IPF did not satisfy a sizable group of patients with IPF that in the past had been lumped with UIP and now currently has begun to be recognized as nonspecific interstitial pneumonia/fibrosis (NIP). There are few reports about the clinical features of NIP.MethodsThe pathologic slides of 66 patients having open lung biopsy (OLB) for the differential diagnosis of interstitial lung diseases (ILD) from 1984 to 1995 were reviewed. Seven cases were confirmed as NIP. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…(1-18)) and UIP patients (lymphocytes 6 (0-38), neutrophils 8.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), eosinophils 5 (0-11)). There was no statistical difference in the total and differential cell counts between the two groups (Mann-Whitney test p=NS for all cell types; fig.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
See 1 more Smart Citation
“…(1-18)) and UIP patients (lymphocytes 6 (0-38), neutrophils 8.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), eosinophils 5 (0-11)). There was no statistical difference in the total and differential cell counts between the two groups (Mann-Whitney test p=NS for all cell types; fig.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
“…In light of the new classification, it can be argued that a BAL lymphocytosis may be suggestive of NSIP, as indicated in the recent ATS statement [3]. In small groups of NSIP patients, not necessarily characterised by the clinical features of IPF, a BAL lymphocytosis has been observed [16][17][18][19]. By contrast DANIIL et al [8] did not find a BAL lymphocytosis in a small cohort of NSIP patients.…”
mentioning
confidence: 99%
“…Later, with the emergence of NSIP as a distinct entity [49], it was suspected that many patients with a BAL lymphocytosis, formerly diagnosed with IPF, did in fact have NSIP. This is supported by the fact that three major East Asian studies showed truly striking lymphocyte levels in NSIP [50][51][52]. It is suggested from high-resolution computed tomography scan observations that those patients might have organising pneumonia/NSIP overlap.…”
Section: Emerging New Findings Immunological Mechanismsmentioning
confidence: 90%
“…Discussion NSIP was first described by Katzenstein and Fiorelli in 1 994 (1). It has been reported that the prognosis of patients with this illness is significantly better than that for patients with UIP (1,5,7,8). Katzenstein and Fiorelli reported that almost 50%of patients completely recovered after steroid therapy and the overall mortality was 1 1 % (1).…”
Section: Case Reportmentioning
confidence: 99%